Children in Conflict with the Law in the Bureau of Jail Management and Penology and Pag-asa (Hope) Youth Center in Iligan City - Palomares, Perla Piedad (Universitas Muhammadiyah Yogyakarta, 2018)
This paper examined the experiences of children in conflict with the law (CICL) in the light of the lower-class-based theories of delinquency and labeling theory. Information on the current circumstances of the youth offender in the local context should prove useful as basis of concrete recommendations for policy decisions and courses of action for those concerned with childrenâs welfare. The same information are vital for agencies and stakeholders in the five pillars of the justice system such as the law enforcement, the prosecution, the court, the penal system and the community.The study focused on the Tipanoy Jail under the BJMP and the Pag-asa (Hope) Youth Centre, the detention and rehabilitation centre of Iligan City. The study covered a total of two semesters.The Lower-Class-Based Theory of Delinquency and the Labelling Theory provided the framework of this study.Â Â These theories explicate why youth offenders seem dominant in the lower-class sector of the population and how devastating the effects of labelling on them as individuals.Data were gathered from a sample of 15 CICL and 15 non-CICL.Â Key informants from the DSWD, PNP, BJMP, RTC as well as parents of CICL were also involved. Personal interview, questionnaire, FGDs and case studies were utilized in data collection In turn, these were analyzed qualitatively whenever necessary and applicable, frequencies and percentages were used and data were displayed in tables and graph. Recommendations were offered based on findings.The findings are as follows: theorized factors such as overcrowding, poor housing, house ownership and type of home (broken home) were found to have influenced the commission of crimes, while migration status, employment status of father and mother were found to have nothing to do with commission of crimes.